High-Endurance UAV for Monitoring Calving Glaciers: Application to the Inglefield Bredning and Eqip Sermia, Greenland - Jouvet, Guillaume; Weidmann, Yvo; van Dongen, Eef; Lüthi, Martin P.; Vieli, Andreas; Ryan, Jonathan C. (Frontiers in Earth Science, 2019)
Unmanned aerial vehicle (UAV) photogrammetry has become an important tool for generating multi-temporal, high-resolution ortho-images and digital elevation models (DEMs) to study glaciers and their dynamics. In polar regions, the roughness of the terrain, strong katabatic winds, unreliability of compass readings, and inaccessibility due to lack of infrastructure pose unique challenges for UAV surveying. To overcome these issues, we developed an open-source, low-cost, high-endurance, fixed-wing UAV equipped with GPS post-processed kinematic for the monitoring of ice dynamics and calving activity at several remote tidewater glaciers located in Greenland. Our custom-built UAV is capable of flying for up to 3 hours or 180 km and is able to produce high spatial resolution (0.25-0.5 m per pixel), accurately geo-referenced (1-2 pixels) ortho-images and DEMs. We used our UAV to perform repeat surveys of six calving glacier termini in north-west in July 2017 and of Eqip Sermia glacier, west Greenland, in July 2018. The endurance of our UAV enabled us to map the termini of up to four tidewater glaciers in one flight and to infer the displacement and calving activity of Eqip Sermia at short (105 minute) timescale. Our study sheds light on the potential of long-range UAVs for continuously monitoring marine-terminating glaciers, enabling short-term processes such as the tidal effects on the ice dynamics, short-lived speed-up events, and the ice fracturing responsible for calving to be investigated at unprecedented resolution.